002.5 Evaluation of five rapid point-of-care tests for syphilis: two treponemal only, and three dual treponemal/hiv assays. (13th September 2015) - Fakile, Y; Hoover, K; Delaney, K; Wesolowski, L; Asef, C; Sun, Y; Park, I; Chow, J; Schapiro, J; Novak, S; Philip, S; Karem, K
Abstract : Background: Traditional syphilis and HIV screening strategies require laboratory capacity which is often limited in resource-poor settings. Affordable rapid point-of-care tests (RPOCT) with high sensitivity and specificity would allow same-day testing and referral for treatment of syphilis and HIV in pregnant women. This would allow a decrease in adverse outcomes as a result of mother-to-child transmission (MTCT). We compared test performance of two RPOCT treponemal tests and three combination treponemal/HIV tests for detection of treponemal antibodies in sera; and we also examined test performance of the three RPOCT treponemal/HIV tests for detection of HIV antibodies in sera. Methods: We tested banked sera previously characterised for syphilis (n = 1186), from San Francisco Department of Public Health, Kaiser Permanente Northern and Southern California, and 437 known HIV-positive samples (CDC HIV), according to manufacturer's insert with 3 dual HIV/Syphilis RPOCT: SD BIOLINE HIV Syphilis Duo (Standard Diagnostics), Multiplo TP/HIV (MedMira) and DPP HIV-syphilis Assay (Chembio), and 2 treponemal-only tests: SD Syphilis 3.0 (Standard Diagnostics), Determine SyphilisTP (Alere). Positive agreement across tests was determined and RPOCT results were compared to prior test results. Results: The 5 assays had concordant positive result of 84% (1362/1623) for treponemal antibodies, and 96.6% (1569/1623) for HIV antibodies. Compared to previously reported results, treponemal tests had sensitivities and specificities of; SD 3.0 – 72%, 97.2%; SD DUO- 72.2%, 97.2%; Multiplo- 80.7%, 88.7%; Chembio – 82.5%, 96.4%; DetermineTP- 89.3%, 97.5%. The 3 treponemal/HIV assays sensitivity was100% for 437 known HIV-positives compared to standard assays. Conclusion: Positive agreement was greater for HIV antibodies than for treponemal antibodies; Using banked sera could have affected performance of treponemal assays. Further prospective studies need to be performed in the field to better characterise performance of RPOCT treponemal tests. Findings from this study will provide data to guide countries' selection of RPOCTs for syphilis and HIV screening. Disclosure of interest statement: The reagents/kits for this study, were donated by the various manufacturers (Standard Diagnostics, MedMira, Chembio, and Alere).